INOVASI PEMANFAATAN SAYURAN MENJADI SMOOTHIE DAN ICE CREAM SAYUR - Nila Widayanti; Santa Maimurni; Dita Sari Mulyadi; Noviana Dwi Putri Ratnasari; Siti Aisyah; Nukmatus Syahria (LPPM Universitas PGRI Adi Buana Surabaya, 2018)
Vegetable is a way of traditional treatment of ancestral heritage that has long been known in Indonesia. Vegetable as a culture of the Indonesian Society desperately needs to be preserved. In an effort to preserve herbs and improve the benefits of herbal medicine in Indonesia, the Division of Work Program